1998
DOI: 10.1111/j.1095-8649.1998.tb00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence length and variation in the mitochondrial control region of two freshwater gobiid fishes belonging to Rhinogobius (Teleostei: Gobioidei)

Abstract: The control region (D-loop) of mitochondrial DNA (mtDNA) was amplified and sequenced for eight samples of the rhinogobies Rhinogobius maculafasciatus and R. giurinus from Taiwan and southern China. The control regions of both species are of 841-842 bp; the length of these sequences being the most compact among all known sequences in teleost fishes. Three conserved sequence blocks (CSB) were observed. The full D-loop and tRNA Phe gene sequences were determined and compared with other fishes. The interspecific s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
0
16
1
Order By: Relevance
“…Several studies of control region in fishes have identified tandemly repeated sequences that vary in copy number among haplotypes (VNTRs; e.g. Chen et al, 1998;Gleeson et al, 1999). In the current study no such VNTRs were detected within species, although there was some evidence of minor length variation among species.…”
Section: Patterns Of Genetic Variation and Repetitive Regionscontrasting
confidence: 48%
“…Several studies of control region in fishes have identified tandemly repeated sequences that vary in copy number among haplotypes (VNTRs; e.g. Chen et al, 1998;Gleeson et al, 1999). In the current study no such VNTRs were detected within species, although there was some evidence of minor length variation among species.…”
Section: Patterns Of Genetic Variation and Repetitive Regionscontrasting
confidence: 48%
“…Interspecific variation between 11·3 and 11·7%, over the entire control region, and 22-34%, at the 5 end, has been reported in two freshwater gobiids (Chen et al, 1998). However, this result, sheds little light on the status of M. cephalus.…”
Section: Taxonomic Implicationsmentioning
confidence: 87%
“…Thus, the phenomenon in P. pavoninus CR corroborates the functional signif icance of this block. Furthermore, in previous studies, more than one TAS cTAS blocks in the CR have been reported, such as two blocks in common carp, Japa nese crucian carp [15] and in two species of Rhinogo bius [47] and three blocks in Myxine glutinosa [48]. Generally, only one block exerts as the termination signal, however, there is no pertinent explanation for the issue of which one of these blocks functions to date.…”
Section: Discussionmentioning
confidence: 99%